(untitled) (International relations and international law Journal, 2020)
The complex geopolitical processes in Eurasia led to the formation of a new format of regional interdependence of all SCO member-states. One of the complex issues are conflicting energy interests of oil and gas suppliers and consumers. The “middle position” of post-Soviet Central Asian states of Eurasia became a natural geopolitical argument in favor of using the territory of CA as a transcontinental “bridge” between the southeastern part of the SCO and Europe. The participation of Russia, China, India and Pakistan in regional energy policy, as well as SCO observer-states is an important component of Eurasian security, which adds a global dimension to the organization. SCO unites on a common platform exporters and importers of energy resources without the involvement of third countries. At the same time, there is a contradictory nature of interaction between all participants of the Shanghai process, which has negative consequences and hinders the development of regional cooperation in Central Asia itself. Many projects within the framework of the Chinese megatrend “One Belt, One Way,” including the active participation of Kazakhstan, indicate the development of the multilateral format. Considering that the source of China’s economic growth is in availability of hydrocarbon resources at the proper level, the policy of China will focus on a wide support of energy projects under SCO. The purpose of this article is to consider the multilateral format of SCO cooperation as one of the possible ways to reduce the risk of contradictions in the field of energy resources and solve problems through participation in joint energy projects. Key words: SCO, energy interests, contradictions, Eurasia geopolitics, Central Asia, SCO Strategy, cooperation.